Internalisasi Nilai Akhlak Kebhinekaan dalam Pembelajaran Akidah Akhlak: Studi Penguatan Sikap Toleransi Peserta Didik - Lutfiah Holifa Balkis; Mahmud Arif (TSAQAFATUNA : Jurnal Ilmu Pendidikan Islam, 2026)
The phenomenon of social, cultural, and religious diversity in Indonesia necessitates the strengthening of tolerance values in education, particularly through value-based learning in Islamic education. However, previous studies indicate that multicultural education tends to remain conceptual and has not sufficiently explored the process of internalizing diversity-based moral values in classroom practices. This study aims to analyze the process of internalizing diversity-based moral values in Aqidah Akhlak learning, the strategies employed by teachers, and their impact on students’ tolerance attitudes. This research adopts a descriptive qualitative approach conducted at MTsN 1 Lahat. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal that value internalization is carried out through integrative approaches, teacher role modeling, habituation, and contextual learning that encourages inclusive social interaction. These findings highlight that value-based Aqidah Akhlak learning plays a strategic role in shaping students’ tolerant character. This study recommends the development of more systematic value-based learning models and further research in broader contexts to strengthen the implementation of multicultural education in Islamic education